Gold Debt-Receivable System with Paddy Rewards Before Debt Repayment: An Islamic Law Perspective - Sulkiah Sulkiah; Zakaria Syafei; Jamaluddin Jamaluddin (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2021)
In fulfillling the needs of life, humans will always need other people around them, like the debt and credit tradition that occurred in Teras Bendung Village, Lebak Wangi Sub-District, a tradition that has long developed and has become the culture of the Teras Bendung village community. Lending gold with guaranteed rice per each harvest, either from rice fields or land products, before the debtor is able to repay the debt, the creditor will withdraw the harvest without reducing the debt burden. The type of research used was field research, where researchers researched directly in the field to obtain reliable data. The data collection techniques were observation, interviews and documentation. The data processing technique was qualitative data analysis, starting with analyzing all the data obtained, after reviewing the next steps are data reduction, data presentation, and drawing conclusions. The results of this research concluded that: the gold debt-receivable system with the provision of rice in return before paying off the debt from the perspective of Islamic law in Teras Bendung Village, Lebak Wangi Sub-District is forbidden. The transfer of responsibility when the debtor dies before paying off the debt will be transferred to the heirs. The consequences for debtors who cannot pay off their debts will get social sanctions, and their assets will be taken over by creditors. Repayment of debt using the exchange rate of goods is usually done by parties who owe, provided that the money is equal to the current price of gold.